Kloning parsial gen penyandi enoil-ACP reduktase dari mesokarp buah kelapa sawit (Elaeis guineensis Jacq.) Partial cloning of gene encoding enoyl-ACP reductase from mesocarp of oil palm (Elaeis guineensis Jacq.) - Asmini BUDIANI; Djoko SANTOSO; Hajrial ASWIDINNOOR; Antonius SUWANTO (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2004)
Summary Enoyl-ACP reductase (ENR) is a component of fatty acid synthase (FAS) that is considered to play an important role in fatty acid elongation and oil accumulation of several plants. One of the proteins expressed coinciding with fruit development and oil accumulation in oil palm has been detected from the previous study and had homology with ENR. Therefore, as a part of genetic engineering program to improve oil content and quality in oil palm mesocarp, this research was aimed to clone cDNA conserved region of gene encoding enoyl-ACP reductase from oil palm mesocarp. Based on the amino acid sequence of the polypeptide that was homologous with ENR and combined with information of conserved region sequences of the same gene from other plant sources, primers were designed for amplifying conserved region of the ENR gene. Amplifi-cation was carried out by RT-PCR using total RNA as template, at several annealing temperatures and MgCl2 concentrations. Amplification product was cloned using pCR 2.1-TOPO, and the sequence was subjected into BlastN analysis. The results confirmed that the cloned cDNA fragment with 698 bp in size was the conserved region of the ENR gene. This sequence was highly homologous with the same gene from other plants such as Oryza sativa, Olea europaea, Brassica napus, Triticum aestivum and Arabidopsis thaliana with E-value 1e-96, 7e-77, 2e-64, 5e-41 and 3e-36, respectively. Based on this result, primers have been made and used to amplify the 5’- and 3’ ends of the ENR -cDNA of oil palm mesocarp. Ringkasan Enoil-ACP reduktase (ENR) merupakan salah satu komponen asam lemak sintase (FAS) yang berperan penting dalam pemanjangan asam lemak dan akumulasi minyak pada berbagai tanaman. Salah satu protein yang ter-ekspresi sejalan dengan tahapan perkembangan buah sawit dan akumulasi minyak pada penelitian sebelumnya diketahui mempunyai homologi dengan ENR. Oleh karena itu, sebagai salah satu bagian dari usaha rekayasa metabolisme minyak pada mesokarp buah sawit, penelitian ini bertujuan untuk mengklon cDNA daerah konservatif gen penyandi ENR dari mesokarp buah sawit. Berdasarkan sekuen asam amino polipeptida yang mempunyai homologi dengan ENR dan dikombinasikan dengan hasil penjajaran daerah konservatif gen tersebut dari berbagai anaman lain, dirancang primer untuk amplifikasi daerah konservatif ENR. Amplifikasi dilakukan dengan RT-PCR menggunakan templat RNA total pada berbagai suhu penempelan dan konsentrasi MgCl2. Hasil amplifikasi dimurnikan dari gel dan diklon menggunakan vektor kloning pCR2.1-TOPO serta dianalisis nya menggunakan BlastN. Hasilnya mengkonfirmasi fragmen cDNA terklon berukuran 698 pb sebagai daerah konservatif ENR tersebut mempunyai homologi tinggi dengan gen yang sama dari O. sativa, O. europaea, B. napus, T. aestivum dan A. thaliana masing-masing dengan E-value 1e-96, 7e-77, 2e-64, 5e-41 dan 3e-36. Berdasarkan hasil tersebut telah dibuat primer spesifik untuk amplifikasi cDNA daerah ujung 5’- dan 3’- gen ENR dari mesokarp kelapa